Consolidated financial statements in light of the Hungarian regulations and the IFRS standards - Szekeres, Alexandra; Dienes, Angelika (Competitio, 2024)
Companies today have diverse relationship systems. In a legal sense, individual companies exercising influence on each other engage in significant transactions with each other during their operations. Market participants require knowledge of the financial, monetary, and income status of these corporate groups. Therefore, in addition to individual annual reports, it is also important to prepare consolidated financial statements that present the group as a single entity, following either national or international accounting standards. In our study, the legal background of consolidation will be presented, as well as the rules of consolidation based on Hungarian regulations and the International Financial Reporting Standards (IFRS). Two IFRS consolidated financial statements will be compared, with a particular focus on the consolidated notes on the accounts (Notes), highlighting those intangible assets whose representation and evaluation are significantly different from Hungarian rules. While the selected parent companies present their corporate groups to varying extents and levels of detail, the requirements of the standards are reflected throughout. JEL code: M40